EFFECTIVENESS OF MANUAL JOINT MOBILIZATION IN FROZEN SHOULDER WITH AND WITHOUT HOME EXERCISE PROGRAM - Amman Ullah Nazir1 , Zavata Afnan2 , Saba Mengal3 , Zainab Shehryar4 , Sharjeel Tasneem5 , Sara Sajjad6 Faisal Basheer7 , Suhail Karim, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: Adhesive Capsulitis or Frozen Shoulder, according to many authors is a clinical disorder rather than Ac diagnosis. OBJECTIVE:To determine the effectiveness of manual joint mobilization in frozen shoulder with and without home exercise program. MATERIALS AND METHODS: A randomized control was conducted in Sindh (Karachi) from May 2022 to November 2022 to determine the effectiveness of manual therapy with and without home exercise program for frozen shoulder. Sample size of 48 participants were randomly assigned to Group A and Group B. Group A and Group B received manual joint mobilization two time per week for total six weeks, Group B advised to perform daily home exercises. The SPADI was used to measure primary outcome was changes in pain and stiffness. Goniometer was used to measure the secondary outcomes. Descriptive and inferential statistics was used for data analysis.RESULTS: Participants were divided into Group A and Group B. Group A (n=24) and Group B (n=24) groups. Results showed that the group B had significantly greater improvements in pain (-25.86 vs. -15.00), disability (-22.64 vs. -17.72), and ROM (39.17 vs 30.01 for flexion, 43.21 vs 33.09 for abduction, and 26.41 vs 18.85 for external rotation) compared to the group A. These findings suggest that joint mobilization with home program may be an effective intervention for improvement in pain, disability, and ROM in patients with shoulder impingement syndrome. CONCLUSION: A Study concluded that Manual joint mobilization with a home exercise program was found to be an effective treatment for frozen shoulder, resulting in significant improvements in pain, disability, and range of motion.